Risk Factors for Sexual Transmission of Hepatitis C Virus Among Human Immunodeficiency Virus-Infected Men Who Have Sex With Men: A Case-Control Study. (6th August 2015) - Vanhommerig, Joost W.; Lambers, Femke A. E.; Schinkel, Janke; Geskus, Ronald B.; Arends, Joop E.; van de Laar, Thijs J. W.; Lauw, Fanny N.; Brinkman, Kees; Gras, Luuk; Rijnders, Bart J. A.; van der Meer, Jan T. M.; Prins, Maria; et al.
Abstract: Background.  Since 2000, incidence of sexually acquired hepatitis C virus (HCV)-infection has increased among human immunodeficiency virus (HIV)-infected men who have sex with men (MSM). To date, few case-control and cohort studies evaluating HCV transmission risk factors were conducted in this population, and most of these studies were initially designed to study HIV-related risk behavior and characteristics. Methods.  From 2009 onwards, HIV-infected MSM with acute HCV infection and controls (HIV-monoinfected MSM) were prospectively included in the MOSAIC (MSM Observational Study of Acute Infection with hepatitis C) study at 5 large HIV outpatient clinics in the Netherlands. Written questionnaires were administered, covering sociodemographics, bloodborne risk factors for HCV infection, sexual behavior, and drug use. Clinical data were acquired through linkage with databases from the Dutch HIV Monitoring Foundation. For this study, determinants of HCV acquisition collected at the inclusion visit were analyzed using logistic regression. Results.  Two hundred thirteen HIV-infected MSM (82 MSM with acute HCV infection and 131 MSM without) were included with a median age of 45.7 years (interquartile range [IQR], 41.0–52.2). Receptive unprotected anal intercourse (adjusted odds ratio [aOR], 5.01; 95% confidence interval [CI], 1.63–15.4), sharing sex toys (aOR, 3.62; 95% CI, 1.04–12.5), unprotected fisting (aOR, 2.57; 95% CI, 1.02–6.44), injecting drugs (aOR, 15.62; 95% CI, 1.27–192.6), sharing straws when snorting drugs (aOR, 3.40; 95% CI, 1.39–8.32), lower CD4 cell count (aOR, 1.75 per cubic root; 95% CI, 1.19–2.58), and recent diagnosis of ulcerative sexually transmitted infection (aOR, 4.82; 95% CI, 1.60–14.53) had significant effects on HCV acquisition. Conclusions.  In this study, both sexual behavior and biological factors appear to independently increase the risk of HCV acquisition among HIV-infected MSM.